Transient Plasma Measured by Fixed Electric Probes in the Scrape‐Off Layer of Korean Superconducting Tokamak Advance Research (KSTAR). Issue 1 (9th January 2013) - Oh, Y.‐S.; Bak, J.‐G.; Woo, H.‐J.; Park, E.‐K.; Kim, H.‐S.; Cho, S.‐G.; Park, S.‐J.; Lho, T.; Chung, K.‐S.
Abstract Transient plasma behavior in the scrape‐off layer(SOL) is analyzed based upon the ion saturation current data measured by ninety‐one fixed electric probes during the second and third campaigns of Korean Superconducting Tokamak Advance Research(KSTAR) operations (2010 ∼ 2011). Experiments are implemented under the following conditions: plasma current of 600 kA, line average density of 6.1× 1019m− 3, Neutral Beam Injection(NBI) power of 1.5 MW, and injection gas of D2. Probes are made of carbon fiber composite(CFC) with a dome shape structure, and extruded about 1 mm from the surface of the background graphite tiles, which are exposed to the strongly magnetized plasma with an incident angle of the particles impinging on the probe from zero to nine degrees. Probes are installed in the limiter and divertor area of the KSTAR device with a bias voltage of ‐315 V in order to measure ion saturation currents. The ion saturation currents from the probes could identify the edge localized mode (ELM) phenomena comparing with D‐alpha signals. In the distribution of the ion saturation currents measured by a probe array during a diverted plasma discharge process, it is found that two strike points move vertically upward and poloidally up and down at the inboard and central divertors, respectively. A comparative study of plasma behavior measured by electric probes is performed with the theoretical predictors of Equilibrium FITing code (EFIT) data (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)